Aptamers and MIPs as alternative molecular recognition elements for vasopressin and oxytocin sensing: A review - Beke, Essohanam; Gondran, Chantal; Chovelon, Benoît; Peyrin, Eric; Holzinger, Michael; Ravelet, Corinne (Biosensors & bioelectronics, 2025)
Arginine vasopressin (AVP) and oxytocin (OT) are two important hormones that regulate various physiological and behavioral functions, such as blood pressure, water balance, social bonding, and stress response. The detection and quantification of these hormones are of great interest in clinical diagnosis and research. However, the conventional methods based on antibodies or enzymes have some limitations, such as high cost, low stability, and ethical issues. Therefore, alternative molecular recognition elements, such as aptamers and molecularly imprinted polymers (MIPs), have been developed to overcome these drawbacks. Aptamers are short nucleic acid sequences that can bind to specific targets with high affinity and specificity, while MIPs are synthetic polymers with imprinted binding sites mimicking natural receptors. Both aptamers and MIPs have advantages such as low cost, high stability, easy synthesis, and modification. In this review, we summarize the recent advances in the development and application of aptamers and MIPs for the sensing of vasopressin and oxytocin, and compare their performances. We also discuss the challenges and future perspectives of aptamers and MIPs as alternative molecular recognition elements for vasopressin and oxytocin sensing. •Review on aptamer- and MIP-based biosensors for the detection of arginine vasopressin and oxytocin.•Presentation of the signaling mechanisms implemented for the development of aptamer and MIP-based biosensors.•Overview of optical, electrochemical and electrical transduction methods.